Stochastic Physiological Gaze-Evoked Nystagmus With Slow Centripetal Drift During Fixational Eye Movements at Small Gaze Eccentricities - Ozawa, Makoto; Suzuki, Yasuyuki; Nomura, Taishin (Frontiers in Human Neuroscience, 2022)
Involuntary eye movement during gaze fixation, referred to as the fixational eye movement (FEM), consists of two types of components: a Brownian-motion-like component called drifts-tremor (DRT) and a ballistic component called microsaccade (MS) with a mean saccadic amplitude of about 0.3° and a mean inter-MS interval of about 0.5 s. During gaze fixation in healthy people at the eccentric position, typically with eccentricity more than 30°, eyes exhibit oscillatory movements alternating between the centripetal drift and the centrifugal saccade with a mean saccadic amplitude of about 1° and a period in the range of 0.5-1.0 s, which has been known as the physiological gaze-evoked nystagmus (GEN). Here, we designed a simple experimental paradigm of gaze fixation at a target shifted horizontally from the front-facing position with less eccentricities. We found a clear tendency of the centripetal DRT and the centrifugal MS as in the GEN, but with more stochasticity and with slower drift velocity compared to the GEN, even during FEM at gaze positions with small eccentricities. Our results showed that the target-shift-dependent balance between DRT and MS achieves the gaze bounded around each of the given targets. In other words, the gaze relaxes slowly with the centripetal DRT toward the front-facing position during inter-MS intervals, as if there always exists a quasi-stable equilibrium posture at the front-facing position, and MS actions pull the gaze intermittently back to the target position in the opposite direction of the DRT.